2020
DOI: 10.1055/a-1103-2038
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transition Period on Performance Parameters in Elite Female Soccer Players

Abstract: AbstractThe purpose of this study was to examine the effect of a 4-week off-season period (transition period) on the anthropometric and performance parameters in elite female soccer players who participated in the UEFA women’s Champions league. Eighteen female players (age 23.6±4.3 years) underwent testing at the end of the competitive period and right after the transition period. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
5
14
0
2
Order By: Relevance
“…However, it is important to analyze the ES for each variable studied, which allows us to observe each phenomenon’s degree of presence, independent of the alpha level calculated [ 52 ]. In this study, like in research by Parpa & Michaelides [ 24 ], all ES in the tests with significant differences in VO 2 max, including men and all data analysis, oscillated between 0.2–0.6. This was considered a small effect.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, it is important to analyze the ES for each variable studied, which allows us to observe each phenomenon’s degree of presence, independent of the alpha level calculated [ 52 ]. In this study, like in research by Parpa & Michaelides [ 24 ], all ES in the tests with significant differences in VO 2 max, including men and all data analysis, oscillated between 0.2–0.6. This was considered a small effect.…”
Section: Discussionsupporting
confidence: 82%
“…As demonstrated in this study, a vacation period without mandatory physical training generates decreases in the VO 2 max [ 37 ] and negatively affects anthropometric parameters [ 51 ]. Therefore, the vacation periods must be adapted into a transition phase [ 24 , 25 ]. In this way, with controlled and directed physical training, both athletes and naval cadets will have optimal physical recovery and maintenance; this condition will allow them to face better the next cycle of physical training [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbopelvic complex and lower limb muscle strength imbalances have been proposed as risk factors for articular or muscular injuries in these players [52]. The quadriceps and hamstring HHD values reported in this research were shown to be greater than those previously reported among elite Cypriot [55] and North American adolescent female football players [54]. Similarly, Farley et al [50] also reported lower hamstring and slightly decreased isometric peak force values among elite female Australian rules football players.…”
Section: Discussionsupporting
confidence: 52%
“…Notwithstanding these findings, in both cases, the values were still below the average of 60 ml/kg · min, which is reported as a minimal satisfactory threshold for elite soccer players [ 26 ]. Research affirms that detraining elicited reductions in VO 2max of professional [ 27 ] and semiprofessional male [ 28 ] players as well as elite female soccer players [ 29 ]. In addition, research indicated that players who followed a training program during the transition period demonstrated lower reductions in VO 2max values compared to those who did not follow any program [ 27 ].…”
Section: Discussionmentioning
confidence: 77%